2013
DOI: 10.4314/ajpsy.v16i3.26
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of clergy in Benin City, Nigeria towards persons with mental illness

Abstract: Objective: The clergy in sub-Saharan Africa play a major role in the care and pathways to orthodox mental health services of the mentally ill. Their attitudes concerning mental illnesses would influence community mental health intervention efforts. This study aimed to determine the attitudes of clergy towards persons with mental illness. Method: A cross-sectional survey of clergy (n= 107) of the Christian and Muslim faiths was conducted, using a socio-demographic questionnaire and the 40-item Community Attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 15 publications
(21 reference statements)
5
22
0
Order By: Relevance
“…Greater religiosity correlated directly with more authoritative attitudes, reflecting oppressive attitudes towards people with mentally illnesses. A similar study in Benin reported more authoritative attitudes among members of the Muslim clergy [20], in consonance with the potential influence of religious beliefs on the perceived stigma of mental illness. The belief that mental illness might indicate spiritual failure potentiates stigma and may discourage individuals from seeking psychiatric care [21].…”
Section: Discussionsupporting
confidence: 61%
“…Greater religiosity correlated directly with more authoritative attitudes, reflecting oppressive attitudes towards people with mentally illnesses. A similar study in Benin reported more authoritative attitudes among members of the Muslim clergy [20], in consonance with the potential influence of religious beliefs on the perceived stigma of mental illness. The belief that mental illness might indicate spiritual failure potentiates stigma and may discourage individuals from seeking psychiatric care [21].…”
Section: Discussionsupporting
confidence: 61%
“…Greater religiosity correlated directly with more authoritative attitudes, reflecting oppressive attitudes towards people with mentally illnesses. A similar study in Benin reported more authoritative attitudes among members of the Muslim clergy [21], in consonance with the potential influence of religious beliefs on the perceived stigma of mental illness. The belief that mental illness might indicate spiritual failure potentiates stigma and may discourage individuals from seeking psychiatric care [22].…”
Section: Discussionsupporting
confidence: 61%
“…Previous researchers studied attitude towards people with mental illness among clergy (Igbinomwanhia, James, & Omoaregba, 2013); medical students (Altindag, Yanik, Ucok, Alptekin, & Ozkan, 2006;Elizur & Rosenheim, 1982 undergraduates (Shruti, Singh, & Kataria, 2016); general public (Yuan, Abdin, Picco, Vaingankar, Shahwan, Jeyagurunathan, & Subramaniam, 2016); psychiatrict/psychiatric nurses (Sun, Fan, Nie, Zhang, Huang, He, & Rosenheck, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Attitude towards people with mental illness is studied in many regions of the world such as Chicago (Watson, Corrigan, & Ottati, 2004); China (Sun, Fan, Nie, Zhang, Huang, He, & Rosenheck, 2014); Hong Kong (China) (Todor, 2013); India (Poreddi, Thimmaiah, & Math, 2015); Israel (Kimhi, Barak, Gutman, Melamed, Zohar, & Barak, 1998); Saudi Arabia (Amira, 2016 (Igbinomwanhia, James, & Omoaregba, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%